Tian Jiu therapy for allergic rhinitis: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Kun, Wai; Zhong, Linda; Dai, Liang; Cheng, Chung-Wah; Lu, Ai-Ping; Bian, Zhao-Xiang
Abstract Background Allergic rhinitis (AR) is one of the most common allergic diseases. The conventional treatments of allergic rhinitis are oral anti-histamines, the use of intranasal corticosteroids, and immunotherapy. Dissatisfied with the ineffectiveness and side effects of these treatments, substantial numbers of patients are turning to alternative treatments like Chinese herbal medicine, particularlyTian Jiu (TJ). TJ is a form of moxibustion in which herbal patches are applied to specific acupoints on the skin. This study aims to investigate the efficacy and safety of TJ in the treatment of allergic rhinitis. Methods/design This will be a prospective, randomized, single-blinded, controlled trial in patients with AR. After a 1-week run-in period, eligible subjects will be randomly assigned to the TJ group, placebo-control group or waitlist-control group. The TJ and placebo-control groups will undergo a 4-week treatment with one session per week and one 4-week post-treatment follow-up. Participants in the waitlist-control group will not receive any treatment during the first 4 weeks but will be required to be assessed. The primary outcome will be the change in the weekly average of the Total Nasal Symptom Score recorded from baseline to the end of treatment. The secondary outcomes will be change in symptoms and change in need for medication between baseline and the end of treatment by using the Rhinitis Quality of Life Questionnaire. Rescue medication (RM) needs will be measured using an RM score, comprising the weekly sum of daily assessments and any form of systemic steroids for allergic rhinitis. Discussion This study will be the first study to compare TJ treatment for allergic rhinitis with a placebo-control group, and a waitlist-control group. The investigation of TJ for allergic rhinitis will also suggest recommendations for clinical practice. The results of this study are expected to provide consolidated evidence for the effectiveness and safety of TJ for the treatment of patients with allergic rhinitis. Trial registration NCT02470845 (17 May 2015).